Deficiency of MecA in Streptococcus mutans Causes Major Defects in Cell Envelope Biogenesis, Cell Division, and Biofilm Formation - De, Arpan; Jorgensen, Ashton N.; Beatty, Wandy L.; Lemos, Jose; Wen, Zezhang T. (Frontiers in Microbiology, 2018)
MecA is an adaptor protein that guides the ClpC/P-mediated proteolysis. A S. mutans MecA-deficient mutant was constructed by double-crossover allelic exchange and analyzed for the effects of such a deficiency on cell biology and biofilm formation. Unlike the wild-type, UA159, the mecA mutant, TW416, formed mucoid and smooth colonies, severely clumped in broth and had a reduced growth rate. Transmission electron microscopy analysis revealed that TW416 grows primarily in chains of giant “swollen” cells with multiple asymmetric septa, unlike the coccoid form of UA159. As compared to UA159, biofilm formation by TW416 was significantly reduced regardless of the carbohydrate sources used for growth (P<0.001). Western blot analysis of TW416 whole cell lysates showed a reduced expression of the glucosyltransferase GtfC and GtfB, as well as the P1 and WapA adhesins providing an explanation for the defective biofilm formation of TW416. When analyzed by a colorimetric assay, the cell wall phosphate of the mutant murein sacculi was almost 20-fold lower than the parent strain (P<0.001). Interestingly, however, when analyzed using immunoblotting of the murein sacculi preps with UA159 whole cell antiserum as a probe, TW416 was shown to possess significantly higher signal intensity as compared to the wild-type. There is also evidence that MecA in S. mutans is more than an adapter protein, although how it modulates the bacterial pathophysiology, including cell envelope biogenesis, cell division, and biofilm formation awaits further investigation.